Coconut tales = 椰爷故事 : grandfather (yeye) stories fo growing up in Singapore - Lim, Jamie (Nanyang Technological University, 2021)
Coconut Tales uses the art of storytelling to retain memories of the past and strengthen the bond between grandparents and their grandchildren. Reminiscence therapy is used to engage seniors and helping them cope with dementia, and guide the story collection process.